Association between sarcopenia and hepatic encephalopathy: A systematic review and meta-analysis - Karn Wijarnpreecha (2020)
© 2019 Fundación Clínica Médica Sur, A.C. Studies have suggested that the presence of sarcopenia in patients with cirrhosis could be a predisposing risk factor for hepatic encephalopathy. This systematic review and meta-analysis were conducted to summarize all available evidence on this relationship. A systematic review was carried out in Medline and EMBASE database through December 2018 to identify studies that recruited patients with cirrhosis from any causes and collected data on the presence of minimal or overt hepatic encephalopathy as well as sarcopenia. All study designs (case–control, cohort and cross-sectional studies) were eligible for the meta-analysis. Odds ratio (OR) and 95% confidence interval (CI) were extracted from the included studies and were pooled together using random-effect, generic inverse variance method of DerSimonian and Laird. Five cross-sectional studies with a total of 1,713 patients met our eligibility criteria and were included into the meta-analysis. We found a significantly higher risk of both mild and overt hepatic encephalopathy among cirrhotic patients with sarcopenia when compared with cirrhotic patients without sarcopenia with the pooled OR of 3.34 (95% CI: 1.68–6.67; I2 = 37%) and 2.05 (95% CI: 1.28–3.29; I2 = 61%), respectively. This systematic review and meta-analysis demonstrated a significant association between sarcopenia and hepatic encephalopathy among patients with cirrhosis.